Preterm lambs given intravenous dopamine show increased dopamine in their cerebrospinal fluid. (3rd January 2014) - Olhager, Elisabeth; Nold‐Petry, Claudia A; Joshi, Mandar S; Doery, James CG; Samarasinghe, Thilini; Walker, Adrian M; Wong, Flora Y
Abstract Aim Dopamine is used as an inotropic medication in preterm infants. The preterm human blood brain barrier (BBB) is permeable to intravascular dopamine, and the impact of exogenous dopamine on the preterm brain remains unknown. The preterm lamb model may be suitable for studying the cerebral impact of dopamine therapy whether its BBB permeability is similar to preterm human infants. We aimed to examine BBB permeability to exogenous dopamine in the preterm lamb, by measuring dopamine levels in the cerebrospinal fluid (CSF). Methods Nine preterm foetal lambs (125–130 days, term = 147 days) were given either dopamine at 10 μg/kg/min (dopamine, n = 4) or saline (control, n = 5). CSF, and plasma samples were taken for dopamine assay. Results The median (range) baseline CSF dopamine level for the combined control and dopamine groups (n = 9) was 0.10(0.03–0.16) ng/mL, and baseline plasma dopamine was 0.30(0.13–0.84) ng/mL. The dopamine lambs showed increase in CSF dopamine to 3.91(1.87–11.35) ng/mL with plasma dopamine increased to 14.2 (9.1–57.9) ng/mL. No change was found in the control lambs. Conclusion In the preterm lamb, the BBB permeability and pharmacokinetics to dopamine infusion are similar to findings in the preterm human infant, supporting applicability of the preterm lamb model for studying effects of dopamine infusion in the preterm human brain.